The Effects of Internationalization of Higher Education on Ethiopian Public Universities: A Critical Review of Literature - Birhanu Sintayehu Alemu; Bayisa Ishetu Gameda; Befekadu Zeleke (Ethiopian Journal of Science and Sustainable Development, 2024)
Internationalization is a process of growth and transformation that responds to environmental changes on a local, regional, national, and worldwide basis. This empirical study aimed to examine the internationalization of higher education in Ethiopia's public universities. To comprehend the policy of internationalization of higher education and draw lessons from theoretical perspectives, three theories; namely, the world society theory, dynamic systems theory and variation theory, were identified and employed. To make the study sound, 40 articles, which were published between 2010 and 2023, in reputable journals and national documents were empirically reviewed. The systematic review shows that through teaching learning, research, technology, partnerships, and student mobility, universities are more globally connected than ever before, expanding beyond national boundaries in the subject of transnational global education. Additionally, the review indicates that, in recent decades, the world's education has undergone great changes from the initiation of the domestic market to internationalization. The study also found that while internationalization offers many benefits to higher education, it carries hazards, such as academic colonialism and challenges in ensuring a high standard of instruction. The internationalization of higher education has a tremendous positive impact on almost all first-generation public universities in Ethiopia since the establishment period to the present. In conclusion, the findings of the review work are vital to educational policymakers in ensuring favourable outcomes for the country in general and the higher education institutions involved, in particular.